Exploring Fantasy Theme Analysis: Unravelling Fandom Dynamics in BTS ARMY - Arny Aurora, Raden; Puspita, Virienia; Maharani, Anissa; Wiranito, Nico (Ridwan Institute, 2024)
In the digital era, fan communities have evolved into sanctuaries of liberation and empowerment, providing enthusiasts with spaces for uninhibited self-expression, diverse perspective exchanges, and identity exploration. Using a qualitative phenomenological approach, the research examines the construction of collective identity and meaning-making among BTS fans.The analysis reveals that the BTS ARMY Indonesia community adopts fantasy themes such as